2021
DOI: 10.3390/insects12060501
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Chitin Synthase Gene in Tetranychus cinnabarinus (Boisduval) and Its Response to Sublethal Concentrations of an Insecticide

Abstract: The carmine spider mite, Tetranychus cinnabarinus (Boisduval), is one of the most important acarine pest species. At present, its control remains primarily dependent on using various chemical insecticides/acaricides in agricultural crops worldwide. To clarify the mechanism whereby T. cinnabarinus responds to insecticide exposure, we identified the chitin synthase 1 gene (TcCHS1) and then explored the gene expression levels of TcCHS1 at different developmental stages of T. cinnabarinus. We also investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Despite the limited number of Chs genes, they are reported to have numerous exons, for example, 24 in Spodoptera exigua, thus being capable of generating multiple alternative splicing variants (Liu, Zhang & Zhu, 2019b). In Crustacea, the number of Chs genes is variable, with cirripedes and copepods having two or more genes with unknown specialisation, while most decapods possess a single Chs gene (Zhang et al, 2021;Xin et al, 2021). Chelicerates also seem to harbour one unique copy (Zhang et al, 2021;Xin et al, 2021).…”
Section: And Organisationmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the limited number of Chs genes, they are reported to have numerous exons, for example, 24 in Spodoptera exigua, thus being capable of generating multiple alternative splicing variants (Liu, Zhang & Zhu, 2019b). In Crustacea, the number of Chs genes is variable, with cirripedes and copepods having two or more genes with unknown specialisation, while most decapods possess a single Chs gene (Zhang et al, 2021;Xin et al, 2021). Chelicerates also seem to harbour one unique copy (Zhang et al, 2021;Xin et al, 2021).…”
Section: And Organisationmentioning
confidence: 99%
“…In Crustacea, the number of Chs genes is variable, with cirripedes and copepods having two or more genes with unknown specialisation, while most decapods possess a single Chs gene (Zhang et al, 2021;Xin et al, 2021). Chelicerates also seem to harbour one unique copy (Zhang et al, 2021;Xin et al, 2021). Unfortunately, chitin synthases seem largely unexplored in spiders, compared to their preliminary explorations in ticks and mites, and information on these genes is also lacking for Myriapoda (Han et al, 2005;Li et al, 2015Liu et al, 2019a;Becchimanzi et al, 2020;Zhang et al, 2021;Song et al, 2021;Yuan et al, 2022b;Chen et al, 2023).…”
Section: And Organisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mythimna separata Walker (Lepidoptera: Noctuidae) is a typical long-distance migratory pest that poses a serious threat to the safe production of maize, wheat, and rice. It has a wide range of occurrences and many generations of damage, leading to crop yield reduction and failure in severe cases. Tetranychus cinnabarinus Boisduval (Acari: Tetranychidae) is one of the most harmful mites in the world of agriculture and forest production, with a short life history, high reproductive capacity, and high resistance to many chemical active ingredients. Blind pesticide abuse frequently occurs in an effort to increase crop yields, and manage pests and illnesses, which results in the emergence of pest resistance , and major environmental pollution issues. Obviously, the development of new pesticides is still on the way. Botanical pesticides can control or obstruct pest development, reproduction, and behavior by nontoxic processes, thereby lowering the use of chemical pesticides, assuring the quality and safety of agricultural goods, and preserving ecological security. Recently, the discovery of novel pesticides from natural products has received much attention. …”
Section: Introductionmentioning
confidence: 99%
“…It is effective against Tetranychus mites, Panonychus mites, and other mites in cotton, fruit trees, flowers, and other crops, especially in killing mite eggs and larvae. , The main mode of action of etoxazole is to inhibit the synthesis of chitin . In recent years, studies have shown that its target may be the sulfonylurea receptor or chitin synthase-1. , Etoxazole is the only commercial acaricide having a 2,4-diphenyl-1,3-oxazoline skeleton. After it was put into the market, the development of acaricides with the same skeleton but higher activity and greater potential has never stopped. Our group has designed and synthesized several series of 2,4-diphenyl-1,3-oxazolines, including those that contain an oxime ether, a thioether, a sulfonate, or a nitrogen-containing heterocycle at the para site of the 4-phenyl of the oxazoline ring, and quite a few compounds (Figure ) were found to exhibit better acaricidal activity than etoxazole. , However, considering the activity and production cost in general, they are not yet practical for industrial development.…”
Section: Introductionmentioning
confidence: 99%